Free coinage of silver - Skinner, Ben (My University, 1891)
Introduction: This subject, although old and threadbare, is almost as far from a satisfactory settlement as it has been anytime during our existence as an independent nation. And just now, when there is so much talk about free silver and the wonderful benefits to be derived there from, it seems highly proper for every voter to study the matter for himself; and see, if he can, whether congress should be upheld or censured for its conservative legislation regarding the relation of gold and silver. “Congress has power to coin money and regulate the value thereof.” This provision seems to give some people the idea that money is money no matter whether it be of sheepskin or of gold; and that the value of such money must remain the same. Within ourselves, of course, we can say what shall constitute a legal lender and what shall not, but when we go outside of our own country, we find that the opinions of other peoples play an important part in the regulation of our money system. The idea that anything that bears a government stamp constitutes good money has been fully refuted by past experience, and the point needs no further remark to convince anyone unless he be a debtor who has argued himself into the belief that anything that will temporarily relieve the crowded class of the country is to be sought after.
Citation: Skinner, Ben. Free coinage of silver. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Economics; Currency; Coinage; Silver; Money; Monetary systems; Theses; Manuscripts (documents)